PARADIGMA PRINSIP HARDSHIP DALAM HUKUM PERJANJIAN PASCA ERA NEW NORMAL DI INDONESIA - Armandhanto, Taufik; Budiarsih, Budiarsih; M, Yovita Arie (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThis journal aims to analyze and discuss about the issuance by government policies related to the Covid-19 pandemic such as Large-Scale Social Restrictions and Social Distancing, which is greatly affecting the performance to implement achievements in the contract, so that some parties can make excuse that there is a force majeure event so the party can terminate the contract. With this situation, it is certainly very important for both party to know and understand the principles of hardship. This research method is normative research which is used to examine the problems that exist in this research. The results of the study found that the rules regarding hardship itself have developed in the practice of international contract law which is regulated in the UNIDROIT Principle of International Commercial Contracts (UPICC) that can be used as a reference in making agreements that have high value and long term. The acknowledgment of its absence of hardship ownin the legal system in Indonesia has made the settlement of cases that related in the hardship category will be settled with the applicable provisions, such as good faith and force majeure. Therefore, contract law in Indonesia is expected to be more adaptive and flexible in relation to changing og circumstances fundamentally by the application of the principle hardship to the legal system in Indonesia.Keywords: contract; force majeure; hardshipAbstrakJurnal ini bertujuan untuk menganalisis dan mendiskusikan mengenai terbitnya kebijakan pemerintah terkait pandemi Covid-19 seperti Pembatasan Sosial Berskala Besar dan Social Distancing, yang tentu saja sangat mempengaruhi kewajiban pelaksanaan prestasi dalam perjanjian, sehingga beberapa pihak dapat beralasan terdapat nya keadaan memaksa sehingga pihak tersebut dapat mengakihiri perjanjian. Dengan adanya keadaan tersebut tentu sangatlah penting bagi para pihak agar dapat mengerti dan memahami mengenai prinsip hardship. Metode penelitian ini bersifat normatif yang digunakan untuk mengkaji problematika yang ada di dalam peneltian ini. Hasil penelitian ini menemukan bahwa aturan mengenai hardship sendiri sudah berkembang di dalam praktik hukum kontrak internasional yang diatur di dalam UNIDROIT Principle of International Commercial Contracts (UPICC) yang dapat dijadikan rujukan dalam melakukan perjanjian-perjanjian yang memiliki nilai yang tinggi serta jangka waktu yang panjang. Belum diakui nya hardship sendiri di dalam sistem hukum di Indonesia membuat penyelesaian perkara yang termasuk kategori hardship diselesaikan dengan ketentuan-ketentuan yang berlaku yaitu itikad baik dan force majeure. Maka dari itu hukum perjanjian di Indonesia diharapkan dapat lebih adaftif serta fleksibel terkait dengan perubahan keadaan secara fundamental dengan diterapkannya prinsip hardship ke dalam sistem hukum di Indonesia.